COOPERATION OF EDUCATIONAL INSTITUTIONS TRAINING INDUSTRIAL PERSONNEL WITH FOREIGN COUNTRIES - Nilufar Pulatovna Esanova (Bright Mind Publishing, 2025)
In today's globalized world, industrial workforce training institutions play a crucial role in economic development. This article examines the significance of international collaboration in vocational education, the benefits of joint training programs, and the challenges faced by institutions. The study highlights successful models from leading countries and provides recommendations for improving cross-border cooperation in industrial workforce development.
Keywords: Industrial workforce training, international cooperation, vocational education, dual education system, global partnerships.